Do Flavonoids Reduce Cardiovascular Disease Incidence or Mortality in US and European Populations? - Peterson, Julia J. (2012)
Twenty publications from twelve prospective cohorts evaluated associations between flavonoid intakes and incidence or mortality from cardiovascular disease among adults in Europe and the United States (US). The most common outcome was coronary heart disease mortality, and four of eight cohort studies reported significant inverse associations for at least one flavonoid class (multivariate adjusted p(trend) <.05). Three of seven cohorts reported that greater flavonoid intake was associated with lower risk of incident stroke. Comparisons were difficult because of variability in the flavonoid classes included, demographic characteristics of the populations, outcomes assessed, and length of follow up. The most common flavonoid classes examined were flavones and flavonols combined (11 studies). Only one study examined all seven flavonoid classes. The flavonol and flavone classes were most strongly associated with lower CHD mortality. Evidence for protection from other flavonoid classes and CVD outcomes was more limited. The hypothesis that flavonoid intakes are associated with lower CVD incidence and mortality requires further study.